IMPLEMENTASI MANAJEMEN KELAS DALAM MENINGKATKAN PRESTASI BELAJAR MURID DI UPTD SDN 184 BATU KECAMATAN PITUMPANUA KABUPATEN WAJO - Andi Rafiah; H. Darmawan; Arisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of classroom management in improving student academic achievement at UPTD SDN 184 Batu, Pitumpanua Subdistrict, Wajo Regency. The study employed a qualitative descriptive approach using field research. The research informants consisted of the school principal, classroom teachers, and parents, who were selected based on their involvement in the learning process. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that classroom management has been implemented through the functions of planning, organizing, leading, controlling, and evaluating. The application of these functions was able to create a conducive learning environment and improve student discipline, participation, motivation, and academic achievement. Supporting factors included teacher competence, support from the school principal, and parental cooperation, while inhibiting factors included differences in student personalities, low discipline among some students, and limited learning resources.